2002
DOI: 10.1016/s0002-9440(10)64446-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between High- and Low-Grade Astrocytoma Using a Human Recombinant Antibody to the Extra Domain-B of Fibronectin

Abstract: Different fibronectin (FN) isoforms are generated by the alternative splicing of the primary FN transcript.We previously demonstrated that the isoform containing the extra domain B sequence of fibronectin (B-FN), a complete type-III-homology repeat, is a marker of angiogenesis that accumulates around neovasculature only during angiogenic processes. We produced a single-chain human recombinant antibody (scFv), L19, which reacts specifically with B-FN and selectively targets tumor vasculature in vivo. We used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
86
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 25 publications
7
86
1
1
Order By: Relevance
“…It is found in association with malignant tumors and is absent in the great majority of mature non-neoplastic tissue (Midulla et al, 2000). Studies of fresh tissue from low-grade and high-grade astrocytomas demonstrate a strong correlation for ED-B isoform of fibronectin with highgrade astrocytomas (Castellani et al, 2002). Thus, identifying an agent that interferes with the permissive remodeling of fibronectin in the ECM in glioblastomas may increase their sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is found in association with malignant tumors and is absent in the great majority of mature non-neoplastic tissue (Midulla et al, 2000). Studies of fresh tissue from low-grade and high-grade astrocytomas demonstrate a strong correlation for ED-B isoform of fibronectin with highgrade astrocytomas (Castellani et al, 2002). Thus, identifying an agent that interferes with the permissive remodeling of fibronectin in the ECM in glioblastomas may increase their sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The FN1 mRNA has three alternative splicing sites termed EDA, EDB (B-FN) and IIICS in human (Kumazaki et al, 1999). B-FN is a marker of angiogenesis that accumulates in blood vessels in highgrade astrocytomas but not in PA (Castellani et al, 2002). Therefore, GBM cells known to express at least three different FN1 receptors a5b1, avb3 or CD44 (Bellail et al, 2004) also secrete FN1, providing both a permissive environment for tumor progression and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The alternatively spliced domains extra domain A (EDA) and extra domain B (EDB) of fibronectin, which are targeted by the F8 and L19 antibodies, respectively, exhibit a high level of conservation among species and are virtually undetectable in normal tissues; however, they are abundantly expressed in the stroma and neovasculature of most aggressive types of human cancers 96,[102][103][104][105][106][107][108][109][110] . Similarly, systematic chemical proteomics studies 107,[111][112][113] have recently shown that another component of the extracellular matrix, periostin, exists in several splice isoforms that are abundantly found in most types of cancers [111][112][113][114] .…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%